PENGARUH ROA, UMUR PERUSAHAAN, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - Sumantri, Dilla Rania Putri; Yuniarwati, Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
During the 2018-2020 timeframe, this study aims to examine the impact of ROA, business age, and firm size on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (ISE). According to the approach of purposive sampling, 77 firms were included in the sample. SPSS (Statistical Product and Service Solution 25) is used in conjunction with Microsoft Excel to do multiple linear regression analysis on the data. ROA appears to be the only element that has a negative and statistically significant impact on tax evasion, while the age and size of the company have a negative and statistically inconsequential impact.